Fantastic Translator Role Models and Where to Find Them: A Longitudinal Perspective on Translation Students’ Possible Selves and Role Model Development - Svahn, Elin (Transletters. International Journal of Translation and Interpreting, 2020)
Drawing on possible selves theory and role model theory, this article explores translation students’ possibilities of envisioning their future as translators. Four MA students in a Swedish university were followed over two years through a longitudinal focus group study. The material was analyzed thematically following Braun and Clarke (2006). The results show that the students discuss themes related to possible selves and role models with both textual and extratextual dimensions, but that the two dimensions do not coincide.